2018
DOI: 10.1159/000494862
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled Related Protein 2 Modulates Epithelial–Mesenchymal Transition and Stemness via Wnt/β-Catenin Signaling in Choriocarcinoma

Abstract: Background/Aims: Choriocarcinoma (CC) is a highly aggressive gestational trophoblastic neoplasia; however, the underlying molecular mechanisms of its invasiveness and metastasis remain poorly understood. Human secreted frizzled-related protein 2 (SFRP2) could function as a tumor promoter or suppressor in different tumors, yet the role it plays in CC’s invasion and metastasis is thoroughly unclear. The current study was aimed to explore the function and underlying mechanism of SFRP2 in CC. Methods: The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Our results showed that chrysophanol inhibited the nuclear localization of β -catenin in FaDu cells ( Figure 3 ), which is in agreement with previous studies [ 35 , 36 ]. Furthermore, we further showed that the phenotype of EMT was reversed by Bml 284, which was consistent with previous studies [ 37 , 38 ]. On the other hand, substantial evidence has shown that Wnt-3 is a key regulator of cell proliferation and metastasis in colorectal cancer, gastric cancer development, and malignant melanoma [ 39 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that chrysophanol inhibited the nuclear localization of β -catenin in FaDu cells ( Figure 3 ), which is in agreement with previous studies [ 35 , 36 ]. Furthermore, we further showed that the phenotype of EMT was reversed by Bml 284, which was consistent with previous studies [ 37 , 38 ]. On the other hand, substantial evidence has shown that Wnt-3 is a key regulator of cell proliferation and metastasis in colorectal cancer, gastric cancer development, and malignant melanoma [ 39 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…When the Wnt ligand binds to the frizzled/lowdensity lipoprotein receptor-related protein (LRP) receptor complex, the Wnt/β-catenin cascade is activated, leading to the accumulation of β-catenin. Conversely, when the Wnt ligands are absent, or the frizzled/LRP receptor complex is blocked by the antagonists, cytoplasmic β-catenin is subsequently recruited to the destruction complex (DC) for degradation [28]. SFRP2 has been viewed as an antagonist of the Wnt/β-catenin pathway due to its homology with the extracellular (See figure on previous page.)…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent pathway analysis showed that hsa-miR-375 was involved in the glypican pathway, regulation of CDC42 activity, CDC42 signaling, developmental biology, Wnt signaling pathway, glypican 3 network, etc. ( Figure S1D), which are highly correlated with immune processes [26] and tumor formation mechanisms [27,28], as well as other diseases [29,30].…”
Section: And S13)mentioning
confidence: 91%